If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(x + 3) = 16 Reorder the terms: -2(3 + x) = 16 (3 * -2 + x * -2) = 16 (-6 + -2x) = 16 Solving -6 + -2x = 16 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + -2x = 16 + 6 Combine like terms: -6 + 6 = 0 0 + -2x = 16 + 6 -2x = 16 + 6 Combine like terms: 16 + 6 = 22 -2x = 22 Divide each side by '-2'. x = -11 Simplifying x = -11
| 11/22x=88 | | x^2+x=-7.75 | | x^2/0.100-x | | 2lgx=lg(9x-20) | | -42x^2-47x+51=0 | | 57=2c+7.5c | | 5x/4-1/3=3 | | lgx=lg(9x-20) | | (y-4)/(y^2-16) | | 3x+10-4x-33=108-16x-100 | | 8(5-s)/5=-2s | | 7x-4=4x-58 | | 2(2z-1)-2(2-3z)=12 | | 5/14+2/14 | | 21=6(x-3) | | log(x+10)=1+log(4x-3) | | 6a-1= | | -3(x-1)-8(x-3)=6x+7-5x | | 5/18+6/18 | | -27=15-12x+30 | | -1=g+8g-28 | | 4/6+1/6 | | 4a-6-=2a+14 | | 1.075(d-0.4d)=85 | | 4ln(x)=16 | | 1/3(x-7)=5x | | 8-x/3=5 | | 6r+7=a | | 219/264 | | 4ln(x)=-16 | | 3/4x=1/2+2/3x | | 6z+12z-18-5z=-12z+4z-11+z |